Family function, anxiety and depression in adults with disabilities: a network analysis - Wang, Bin; Yuan, Dongling; Zhong, Xiao; Yang, Fan; Fu, Haojie (Frontiers in Public Health, 2023)
Background The prevalence of family dysfunction, anxiety and depression is high in people with disabilities due to long-term activity constraints and social difficulties. Recently, although studies have attempted to provide guidance for family therapy by focusing on the relationship between family function and negative emotions, the specific effects of improved family function during family therapy on alleviation of anxiety and depressive symptoms have been obscured. Thus, this study attempted to elucidate the impact of specific family functioning on specific symptoms of anxiety and depression through network analysis. Methods Family APGAR Index Questionnaire (APGAR), Generalized Anxiety Scale (GAD-7), and Patient Health Questionnaire Depression Scale (PHQ-9) were used to survey 897 adults with disabilities in Sichuan Province. Meanwhile, network analysis for studying the relationship between anxiety, depression and family functioning among the disabled via R software. Results The network analysis showed that (1) Nodes PHQ4 (“Energy”), APGAR3 (“Growth”), GAD1 (“Nervousness”) and GAD4 (“Relaxing Trouble”) were central nodes in the network model; (2) Bridge nodes linking family function, anxiety and depressive symptoms in the sample were PHQ9 (“Suicide ideation”), PHQ6 (“Worthlessness”), GAD1 (“Nervousness”) and GAD5 (“Restlessness”); (3) The node APGAR5 (“Resolve”) directly connects the bridge symptoms PHQ9 (“Suicide ideation”) and PHQ8 (“Motor”). Conclusion This study suggests that therapists could target the resolve of family members during family therapy to reduce suicidal ideation and enhance the level of activity of people with disabilities, thereby improving the network of anxiety and depression symptoms and alleviating negative emotions of people with disabilities.